Relative match intensities at high altitude in highly-trained young soccer players (ISA3600) - Buchheit, M.; Hammond, K.; Bourdon, P. C.; Simpson, B. M.; Garvican-Lewis, L. A.; Schmidt, W. F.; Gore, C. J.; Aughey, R. J. (Journal of Sports Science & Medicine, 2015)
To compare relative match intensities of sea-level versus high altitude native soccer players during a 2-week camp at 3600 m, data from 7 sea-level (Australian U17 National team, AUS) and 6 high-altitude (a Bolivian U18 team, BOL) native soccer players were analysed. Two matches were played at sea-level and three at 3600 m on Days 1, 6 and 13. The Yo-Yo Intermittent recovery test (vYo-YoIR1) was performed at sea-level, and on Days 3 and 10. Match activity profiles were measured via 10-Hz GPS. Distance covered >14.4 km.h-1 (D>14.4 km·h-1) and >80% of vYo-YoIR1 (D>80%vYo-YoIR1) were examined. Upon arrival at altitude, there was a greater decrement in vYo-YoIR1 (Cohen`s d +1.0, 90%CL ± 0.8) and D>14.4 km·h-1 (+0.5 ± 0.8) in AUS. D>14.4 km.h-1 was similarly reduced relative to vYo- YoIR1 in both groups, so that D>80%vYo-YoIR1 remained similarly unchanged (-0.1 ± 0.8). Throughout the altitude sojourn, vYo-YoIR1 and D>14.4 km·h-1 increased in parallel in AUS, so that D>80%vYo-YoIR1 remained stable in AUS (+6.0%/match, 90%CL ± 6.7); conversely D>80%vYo-YoIR1 decreased largely in BOL (-12.2%/match ± 6.2). In sea-level natives competing at high-altitude, changes in match running performance likely follow those in high-intensity running performance. Bolivian data confirm that increases in `fitness` do not necessarily translate into greater match running